Changes in the common carotid blood velocity waveform for exercise training - Noor Azmi, Azran Azhim; Kamiya, Tatsuaki; Katai, Mizuki; Akutagawa, Masatake; Hirao, Yuji; Yoshizaki, Kazuo; Nomura, Masaharu; Obara, Shigeru; Tanaka, Hiroyuki; Yamaguchi, Hisao; Kinouchi, Yohsuke (Springer Berlin Heidelberg, 2007)
We investigated the common carotid artery (CCA) blood flow velocity in 5 healthy sedentary subjects using continuous wave (CW) Doppler ultrasound velocimeter which developed in our laboratory. The present study aimed to investigate non-invasively the effects of a short-term 4 week aerobic training program on the resting CCA blood velocity waveforms and heart rate. The CCA blood velocities were measured for 3 minutes at resting sitting posture with synchronized measurement of electrocardiogram (ECG) and brachial blood pressure (BP). Training exercise significantly enhanced all blood velocity waveforms with decreasing of heart rate. Systolic blood pressure (SBP) changed with training in the young sedentary subjects, but there is not significant change in diastolic and its mean blood pressure. The evidence of improvement in training was reinforced by a significant reduction in peripheral vascular resistance and improvement in vagal function. We conclude that short-term training improves cardiovascular and autonomic function in these subjects, and training effect may be simply evaluated using the non-invasive measurement system of blood velocity in CCA.